Collaborative Encyclopedia of Algorithms - Algpedia - Viana, Thais N.; da Silva, João C. P.; Delgado, Carla A. D. M.; Martins, Carlos Eduardo da S.; Gouvêa, Fernando R. (Anais do Workshop sobre Educação em Computação (WEI); 2017: Anais do XXV Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2017.3544, 2017)
The process of building and sharing knowledge gained ground in academic research in the last decade, as more participative ways of learning became feasible. Difficult learning tasks, like learning how to program, can now count with technological support for more democratic ways of learning. In this article we present AlgPedia, a free encyclopedia about algorithms and programs in a wiki format. Algpedia's goal is to serve information not only to humans but also to other programs. Regarding human usage, AlgPedia's intent is to support and encourage the creation of collaborative content, besides helping the software developers' community to find the best algorithmic solutions and the best suited implementations for their problems. Behind the wiki interface, the AlgPedia web platform supports a semantic database that can be accessed by intelligent non-human agents.